ASSOCIATION BETWEEN SOCIAL SUPPORT AND ANXIETY AMONG PREGNANT WOMEN IN DURING THE CORONAVIRUS DISEASE 2019 (COVID-19) PANDEMIC IN PARE DISTRICT - Dina, Dina Zakiyyatul Fuadah (Journal of Global Research in Public Health, 2021)
Background: Coronavirus disease 2019 (COVID-19) is a public health emergency of international concern and poses a threat to the mental health of pregnant women. Aim: The purpose of this study was to determine the relationship between social support and anxiety among pregnant women during the Covid-19 pandemic in Pare District, Indonesia. Methods: From 9 to 21 March 2021, an online survey was conducted, which collected the information on demographic data, anxiety, social support to COVID-19 of women with established medical records in the Community Health Center of Pare, District. Anxiety was assessed by the Pregnancy-Related Anxiety Questionnaire-revised (PRAQ-2) questionnaire, social support was assessed by the Social Support Questionnaire. Results: This study had 37 participants with most of them 20-30 years old. During the period of prevention and control of the epidemic, all the pregnant women adopted protective measures, such as wearing masks, washing hands frequently, and staying at home. The results of Social Support most pregnant (89.2) were in the high category and anxiety in pregnant the majority (64.9%) in the medium category. Analysis using the Spearman rank test, the results of p-value = 0.000 (< 0.05). The strength of the relationship between variables is indicated by the value of r = 0.570 Conclusion: Pregnant women's anxiety is affected by the readiness of pregnant women to face childbirth, knowledge of pregnant women, and level of education. It is hoped that pregnant women can manage their anxiety during the Covid-19 pandemic improving the quality of relationships with husbands and family members. Keywords: Social support, anxiety, pregnant women, COVID-19